Diabetes and Pancreatic Cancer - Hsu, Christine; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Pancreatic cancer is the fourth leading cause of cancer death in the United States. Risk factors for pancreatic cancer are smoking, family history, chronic pancreatitis, and diabetes. There is controversy with regards to the causal relationship between diabetes and pancreatic cancer because many patients with pancreatic cancer have new onset diabetes. Abstracts presented at the 2011 American Society of Clinical Oncology (ASCO) Annual Meeting highlighted and supported the positive association between pancreatic cancer and diabetes. Abstract #4102 reports a two-fold risk of pancreatic cancer in diabetic patients. Abstract #4063 also presented at the 2011 ASCO Meeting shows that metformin prolongs survival and decreases risk of death in patients with pancreatic malignancy and diabetes. Image: Metformin disrupts G protein-coupled receptor and insulin signaling and pancreatic cancer growth.